Salud Mental Descrita desde un Enfoque Diferencial en Pacientes Gestantes de una Institución de Salud en el Municipio de Uribía (2023)
Mental health is considered by the mental health observatory and the World Health Organization (WHO) as a public health problem and stipulates that it is the disease of the 21st century, which affects a large part of the population; For this reason, through the following research, we intend to describe the mental health status of pregnant patients who are users of a health institution in the municipality of Uribía, taking into account the differential approach, in which the quantitative, cross-sectional method was implemented. and descriptive type, the data collection instruments, the SQR mental health screening, were used for the research. Likewise, a second instrument called the HADS Hospital Anxiety and Depression Scale was implemented; the sample was made up of 200 pregnant women assigned to the medical programs of the State Social Enterprise Hospital Nuestra Señora del Perpetuo in the municipality of Uribía.